Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T16:15:20+01:00
Przykład 1:
x-y=7 / -y
8x+6y=42

x=7+y
8(7+y) +6y=42
56+8y+6y=42
56+14y=42
14y=-14
y=-1
x=7+(-1)=7-1=6
x=6
y=-1

Przykład 2:
x+3y=4 /-3y
5x+2y=7

x=4-3y
5(4-3y)+2y=7
20-15y+2y=7
-13y=-13
y=1
x=4-3*1=4-3=1
x=1
y=1
  • fibi
  • Rozwiązujący
2009-12-09T16:17:10+01:00
1.
x=7+y
8(7+y)+6y=42
56+8y +6y =42
14y = 42- 56
14y = - 14 / : 14
y = -1
x = 7-1

x=6
y= -1

2.
x=4-3y
5x+2y=7
5(4-3y) +2y=7
20 -15y +2y = 7
13y= -13
y = -1
x = 4+3


2009-12-09T16:18:13+01:00
X-y=7
8x+6y=42 Ipodzielić na 6

x-y=7
8/6x+y=7

x-y+4/3x+y=14
3 1/3x=14 Ipodzielić na 3 1/3
x=4 1/5

4 1/5 - y=7
-y=7-4 1/5
-y= 2 4/5
y= -2 4/5

2.
x+3y=4
5x+2y=7 Ipodzielić na -5

x+3y=4
-x-2/5y=-7/5

x+3y-x-2/5y= 4-7/5
2 3/5y= 2 3/5
y=1

x+3=4
x=1